"Tis a pity she's a whore": An Actress and her Doubles between postcommunism and posthumanism - Čale Feldman, Lada (2001)
The article discusses the fate of two Croatian actresses in the Croatina nineties, focusing primarily on the discursive production of their anathema or deification. Using the parameters of Rene Girard's anthropology, the analysis attempts to discover the logic of obsessive discursive doubling of these two figures, in media and both high-brow and low-brow, local and global imagination.
Projekt MZOS
ENG